Structural, textural and electrochemical relationships in HF etched cobalt-silicon micro/mesoporous oxycarbides. Issue 7 (May 2020) - Tamayo, Aitana; Rodriguez, M Angeles; Colomer, M. Teresa; Sanchez, Elizabeth; Mazo, M. Alejandra; Rubio, Juan; Rubio, Fausto
Abstract: Cobalt-silicon oxycarbide materials (Co–SiOC) have been produced through the polymer-derived ceramic route by incorporating Cobalt acetate in different proportions. HF etching of the obtained materials leads to obtaining C-rich Co–SiOC materials where the constituent phases present different characteristics. The SiO2 units that were the most vulnerable to the chemical attack were the most tensioned ones which are connected at the edges of the graphitic planes. The carbonaceous nanostructures in the HF-etched materials present a different ordering degree which is related with the microstructural characteristics of the pyrolyzed precursors. In addition, the electrochemical performance turns out to be dependent not solely on the Co content but also to the graphitization degree of the carbonaceous phase.